The efficacy of the homoeopathic similimum in the treatment of climacteric symptoms - Bengis, Zoe (2012)
M.Tech. === Menopause refers to the natural cessation of the menstrual cycle at the end of the reproductive years, and is usually defined retrospectively after twelve consecutive months of amenorrhoea. Climacteric is the term used to describe the life period surrounding menopause. It begins with physiological changes that mark the transition between the reproductive and post-reproductive years (Lewis and Bernstein, 1996). The mean age of menopause is 51 years, with a normal range from 45 to 56 years (Chamberlain and Malvern, 1996). There are many symptoms associated with menopause, including hot flushes and night sweats, headaches, sleep difficulties, vaginal dryness and loss of libido, urinary problems, joint and muscle pains, depression, irritability, and poor memory and concentration. Long-term risks and effects include osteoporosis and coronary heart disease (MacGregor, 2000). The aim of this study was to determine the efficacy of the homoeopathic similimum in the treatment of climacteric symptoms. The research study was advertised in local newspapers, pharmacies, and on the Doornfontein campus of the University of Johannesburg in order to recruit volunteers for the study. All volunteers were required to complete a Suitability Criteria Questionnaire. Following this, ten participants were selected who met the inclusion criteria. The study involved four homoeopathic consultations for each participant over a period of three months. During the first consultation a consent form was completed, the procedures of the research were explained to the participant, a full case history was taken, and a physical examination was performed. According to each participant’s individualized physical, mental and emotional symptoms ascertained from the case history, the researcher determined a suitable similimum remedy. A similimum remedy can be defined as the single remedy that fits the symptom picture (Digby, 1997). The abbreviated Kupperman Menopause Index was completed by each participant at the beginning of the treatment, and then at four-weekly intervals for the duration of the twelve week trial. The results were then transferred to the participants’ main Kupperman Menopause Index and compared, thus determining the effect of the homoeopathic similimum in treating climacteric symptoms.